Dual activity cavitation reactors for increased efficacy in degradation of refractory pollutants-A case study on cephalexin degradation - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical Engineering Research & Design, 2023)
The present work discloses a new form of cavitation processes using reactors of dual activity for increased efficiency. A proof of concept is established for the degradation of a refractory pollutant-cephalexin using both conventional and dual function cavitation reactors for the first time using acoustic and hydrodynamic cavitation (HC). A vortex diode as a cavitating device was employed for HC using aluminium as a non-catalytic and copper as dual function device for providing additional catalytic effect. The process in-tensification using hydrogen peroxide (H2O2) coupled with the dual function devices was highly effective. A negligible degradation with only HC and 81% for HC coupled with H2O2 in 60 min for Al-vortex diode compared to 100% degradation in only 5 min for the copper device clearly demonstrates the order of magnitude enhancements establishing dual function due to catalytic activity. Also, pH modification (pH 11) yields enhancement over 300% for Cu-vortex diode. The use of dual function reactors drastically reduces H2O2 do-sage. The overall enhancements in the per pass degradation and cavitation yields were huge, similar to 3000% and 1450% respectively, highlighting the potential of the dual function ca-vitation reactors in real-life applications, not just for increased efficiencies but also for significantly reduced costs.(c) 2023 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Advanced oxidation; Degradation; pollution; Technology; Wastewater treatment